The Tradition of Frigate Mackerel (Auxis thazard) Processing as Balinese Local Wisdom - I Gde Suranaya Pandit (Scopus ID: 57205029330) (SEAS (Sustainable Environment Agricultural Science), 2019)
Bali is a small island that is a world tourist destination. Bali is surrounded by ocean. The ocean has an enormous potential in the fishery field. One of the fish potentials is frigate mackerel. This research aims to describe the handling process and the processing of frigate mackerel in the central of fish boiling, Kusamba village, Bali. This research is designed in an observational descriptive study. Observation conducted on the handling process and the processing of frigate mackerel from its catching located at Amed beach, take a three-hour drive to Kusamba until the processing to be a boil frigate mackerel in the central of fish boiling Kusamba village. Quality test of frigate mackerel processed results at Kusamba Village consists of microbiological, chemical, and organoleptic quality conducted at the laboratory of fisheries and marine of Bali Province. Observation results will be elaborated qualitatively in the photos form and narratives, laboratory results are described in tables and analyzed using Indonesian national standards. The results showed that the process of frigate mackerel handling in Bali is still using a simple method with traditional equipment. Although by using simple equipment, the quality of the boil fish product of Kusamba village is proven has a good quality and meet the Indonesian national standards.